An Italian multicentre validation study of the coma recovery scale-revised - Estraneo, A; Moretta, P; De Tanti, A; Gatta, G; Giacino, J T; Trojano, L (European journal of physical and rehabilitation medicine, 2015)
Rate of misdiagnosis of disorders of consciousness (DoC) can be reduced by employing validated clinical diagnostic tools, such as the Coma Recovery Scale-Revised (CRS-R). An Italian version of the CRS-R has been recently developed, but its applicability across different clinical settings, and its concurrent validity and diagnostic sensitivity have not been estimated yet. To perform a multicentre validation study of the Italian version of the Coma Recovery Scale-Revised (CRS-R). Analysis of inter-rater reliability, concurrent validity and diagnostic sensitivity of the scale. One Intensive Care Unit, 8 Post-acute rehabilitation centres and 2 Long-term facilities Twenty-seven professionals (physicians, N.=11; psychologists, N.=5; physiotherapists, N.=3; speech therapists, N.=6; nurses, N.=2) from 11 Italian Centres. CRS-R and Disability Rating Scale (DRS) applied to 122 patients with clinical diagnosis of Vegetative State (VS) or Minimally Conscious State (MCS). CRS-R has good-to-excellent inter-rater reliability for all subscales, particularly for the communication subscale. The Italian version of the CRS-R showed a high sensitivity and specificity in detecting MCS with reference to clinical consensus diagnosis. The CRS-R showed good concurrent validity with the Disability Rating Scale, which had very low specificity with reference to clinical consensus diagnosis. The Italian version of the CRS-R is a valid scale for use from the sub-acute to chronic stages of DoC. It can be administered reliably by all members of the rehabilitation team with different specialties, levels of experience and settings. The present study promote use of the Italian version of the CRS-R to improve diagnosis of DoC patients, and plan tailored rehabilitation treatment.